The Synergetic Effect of Ni and Fe Bi-metal Single Atom Catalysts on Graphene for Highly Efficient Oxygen Evolution Reaction - Xu, Yingqi; Zhang, Weifeng; Li, Yaguang; Lu, Pengfei; Wang, Yi; Wu, Zhong-Shuai (Frontiers in Materials, 2019)
Oxygen evolution reaction (OER) is key for electrochemical water splitting. Catalysts minimized in single-atom level (SACs) anchored on two-dimensional substances are highly active for various electrocatalytic reactions, but so far represent the limited performance for OER. Herein we report a general strategy for the fabrication of bi-metal Ni and Fe SACs loaded on graphene to significantly boost the OER activity. Notably, this unique structure of single Ni and Fe atoms co-existed on graphene has a strong synergetic effect, which can substantially elevate the charge transfer of catalysts. As a result, the obtained bi-metal SACs with the appropriate ratio of 4 for single Ni and Fe atoms show a small overpotential of 247 mV at 10 mA·cm−2 of OER current density in KOH electrolyte, outperforming individual-metal Ni (329 mV) or Fe (384 mV) SACs. Furthermore, such catalyst exhibits excellent stability without significant decay with increasing time at high current of 20 mA·cm−2 continuously for 48 hours. This work provides a new avenue for regulating the properties of transition metal SACs on graphene for water electrolysis.